If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = 2x + 15 Reorder the terms: 41 = 15 + 2x Solving 41 = 15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 41 + -2x = 15 + 2x + -2x Combine like terms: 2x + -2x = 0 41 + -2x = 15 + 0 41 + -2x = 15 Add '-41' to each side of the equation. 41 + -41 + -2x = 15 + -41 Combine like terms: 41 + -41 = 0 0 + -2x = 15 + -41 -2x = 15 + -41 Combine like terms: 15 + -41 = -26 -2x = -26 Divide each side by '-2'. x = 13 Simplifying x = 13
| -3x+9=6x-99 | | 2(u-8)-8u=-28 | | 50+5x=3x-40 | | 20x=380 | | 18x+7=400+5x | | 4x+3/4=-10 | | 4w+2w=18 | | 7-4(2t-7)=-21 | | 2y+8=180 | | 2(3v+8)=70 | | 17y+2x=-29 | | 7x+8-9x=14-15x+13x-6 | | -5(-6w+2)-6w=6(w-2)-8 | | 2=3x+14 | | (12g^1)= | | -6=2u+6 | | 72n+28=1 | | -9x^2+43x+10=0 | | 7t-6=5t-2 | | -u+5(u+4)=38 | | 87=4y+11 | | 6x+3=-5x-107 | | -24+x=x+24 | | -6=6(u-2) | | 2(5x-8)=3(2x-1) | | x^3+8x=561 | | 3x+6=x+26 | | b^2-5b+6=0 | | 59-(5x+5)=5(x+2)+2 | | 6/-5+8/7 | | 8=m-6+b | | x^2-2x+5=22 |